E-LKS BERBASIS STEM (SCIENCE TECHNOLOGY ENGINEERING MATHEMATIC) PADA MATERI SISTEM PERNAPASAN KELAS XI SEKOLAH MENENGAH ATAS - Ospa Pea Yuanita Meishanti; Hanik Lutfiyah (Khazanah Pendidikan, 2021)
E-LKS is one example of media from technological developments that can improve the quality of the learning process, especially in the current era of the covid-19 pandemic due to the need for creative, innovative teachers in learning, so that online learning can increase students' interest in learning. In this study, researchers will develop an e-LKS based on STEM (Science Technology Engineering Mathematical) on respiratory system material for class XI. STEM is a learning approach that involves the application, knowledge, skills and values to solve or solve problems in the context of everyday life, or explore, investigate, and solve problems related to real life. The purpose of developing this media is to determine the feasibility of the media from material experts, media experts and find out the attractiveness of the media through questionnaire responses from students. The research method uses a 4D model. This development model is divided into four stages, namely: define, design, develop, disseminate, with material expert validation results of 78.33% with appropriate criteria, media expert validation obtained 88.88% with very feasible criteria and student response questionnaires of 80.20% with attractive media criteria, so that the media is feasible and interesting to be used as another reference that supports the learning process.